From cosmos to canvas: Interpreting arts education through the poetics methods of Ahmad Sadali’s Islamic art - Haq, Mochamad Ziaul; Sugiharto, Ignatius Bambang (Indonesian Research Journal in Education |IRJE|, 2025)
This study interpreted Ahmad Sadali’s Islamic art poetics as a conceptual and pedagogical framework for spiritually grounded art education. Drawing on Sadali’s writings and artworks, the study employed a narrative literature review with hermeneutic analysis to explore how his creative process, rooted in tawhid (Islamic monotheism), contemplation, and inner spirituality, can inform contemporary Islamic art pedagogy. Sadali views artistic creation as visual dhikr (remembrance of God), emphasizing the intrinsic-internal environment as the source of creativity. His approach bridges aesthetics and spirituality, positioning art as a worship medium and moral reflection. The study found that integrating Sadali’s poetics into arts education promotes character formation, spiritual awareness, and ethical sensitivity, offering a transformative learning model. It concludes that Sadali’s thought provides theoretical and methodological contributions to value-based Islamic art education, aligning artistic practice with deeper metaphysical and cosmological understanding.